Biblical and Semitic studies;: critical and historical essays by the members of the Semitic and Biblical faculty of Yale university (Yale bicentennial publications, 1901)
.--Curtis, E. L. The tribes of Israel.--Kent, C.F. The growth of Israelitish law [by] C. F. Kent and F.D. Sanders.--Porter, F. C. The Yecer Hara; a study in the Jewish doctrine of sin.--Moulton, W. J. The significance of the transfiguration.--Bacon, B. W. Stephen's speech: its argument and dactrinal relationship.--Torrey, C C. The Mohammendan conquest of Egypt and North Africa.